PENERAPAN PEMBELAJARAN TEMATIK INTEGRATIF DALAM PEMBELAJARAN PKN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V SD - Mega Puspita Sari (Universitas Muhammadiyah Gresik, 2020)
Learning Civics in primary schools aims to equip and develop attitudes and moral values in students. The teacher's role is very important in the Civics learning process. Learning Civics in Primary Schools should not be a learning problem for students. But in reality the activities and completeness of student learning outcomes in class V SDN Gembong 1 are still not satisfactory. Students tend to be passive and lazy to follow civics learning, and student learning outcomes are under mastery learning. This is because Civics learning is not presented in an integrative thematic way. Efforts are being made to overcome the problem of Civics learning in class V SDN Gembong 1 is to implement integrative thematic learning on the theme of the sub-theme Relationship between Living Things and the Unity and Unity material Ecosystems. This study aims to improve the activities and learning outcomes of fifth grade students in Civics Education at SDN Gembong 1 Lamongan Regency.This research uses classroom action research (CAR) with a collaboration model. The subjects in this study were all fifth grade students of Gembong 1 Elementary School in Lamongan Regency, with research procedures (1) Planning, (2) Action, (3) Observation, (4) Reflection in each cycle. The instruments in this study were (1) observation sheet of learning activities, (2) formative test questions (3) documentation tools. The results showed that the implementation of integrative thematic learning can improve student learningactivities and outcomes. Increased student learning activities can be seen by observing when learning isapplied according to integrative thematic procedures. While the improvement in student learning outcomes isknown from the acquisition of formative test assessments. Improved learning outcomes from before the action,cycle I and cycle II, namely from completeness of students before the action is 44% increased to a value of65% and in the second cycle increased to 76% so that the percentage increase in student learning outcomesfrom before the action to cycle II is equal to 32%. These results indicate that the application of integrativethematic learning in Civics learning in fifth grade students of SDN Gembonng 1, Lamongan Regency canimprove student learning activities and outcomes